Affinity capillary electrophoresis and quantum mechanical calculations applied to investigation of [Gly6 ]-antamanide binding with sodium and potassium ions - Pangavhane, Sachin; Böhm, Stanislav; Makrlík, Emanuel; Ruzza, Paolo; Kašička, Václav (Electrophoresis, 2017)
ACE in a free solution and quantum mechanical density functional theory have been applied to the investigation of interactions of glycine-6-antamanide ([Gly6 ]AA), a synthetic derivative of cyclic decapeptide antamanide isolated from the highly poisonous mushroom Amanita phalloides, with sodium or potassium ions in methanol. First, from the dependence of effective electrophoretic mobility of [Gly6 ]AA on Na+ or K+ ions concentration in the BGE (methanolic solution of 20 mM chloroacetic acid, 10 mM Tris, pHMeOH 7.8, containing 0-50 mM NaCl or 0-40 mM KCl), the apparent binding (stability) constants of [Gly6 ]AA-Na+ and [Gly6 ]AA-K+ complexes were evaluated as 26 ± 1 and 14 ± 1 L/mol, respectively. The employed ACE method included correction of the effective mobilities measured at ambient temperature and at variable ionic strength of the BGEs to the mobilities related to the reference temperature 25°C and to the constant ionic strength 10 mM. Second, the interaction energies of the [Gly6 ]AA-Na+ and [Gly6 ]AA-K+ complexes (-466.3 and -345.2 kJ/mol, respectively) and the structural details of these complexes, such as position of the Na+ and K+ ions in the cavity of the [Gly6 ]AA molecule and the interatomic distances within these complexes, were determined by the density functional theory calculations.
Keywords: Models, Molecular; methanol; Sodium; draslík; Temperature; [Gly6]-antamanide; Potassium; Electrophoresis, Capillary; Density functional theory; teplota; vazebná místa; molekulární modely; Binding Sites; osmolární koncentrace; elektroforéza kapilární; cyklické peptidy; Peptides, Cyclic; Stability constant; Affinity capillary electrophoresis; sodík; Methanol; Peptide complex; Osmolar Concentration